Determining the effect of drug "Warfarin sodium" on toxicity indicators in an acute experiment - D.O. Hlavachek; O.Ye. Kondratenko (Medičnì Perspektivi)
The drug "Warfarin sodium" refers to anticoagulants of indirect action. It contains only one substance - warfarin sodium, the toxicological indicator of which have been studied in many countries. Therefore, the range of indicators for DL50 of warfarin sodium is very large. However, warfarin sodium has not yet been studied in Ukraine, its maximum permissible concentration in the air of the work area has not been established. Significant volumes of production and use of the drug “Warfarin sodium” on the territory of Ukraine necessitate the clarification of its main toxicological indicators and the establishment of the maximum allowable concentration in the air of the working area, which includes several stages. The first of them is the purpose of this work, namely: to establish DL50 upon intragastric administration of the drug "Warfarin sodium" to two species of animals in the conditions of an acute experiment. Experimental animals (60 non-linear white rats and 70 non-linear white mice) were divided into 9 groups. Six groups were injected with the drug "Warfarin sodium" in different doses: the first group (female rats) – 58 mg/kg per animal, the second (also female rats) – 29 mg/kg, the third (male rats) – 323 mg/kg, the fourth (also male rats) – 161.5 mg/kg, the fifth (mice of both sexes) – 374 mg/kg, the sixth (also mice of both sexes) – 187 mg/kg. Three control groups (the first – 6 male rats, the second – 6 female rats, the third – 14 mice) received distilled water. As a result, the mortality rates of experimental animals were obtained, on the basis of which, using the probit analysis method, the toxicity indicator of DL50 was determined: for female rats – 15.85 mg/kg, male rats – 398.11 mg/kg and mice –645.65 mg/kg. The established DL50 for male rats after intragastric administration of the drug "Warfarin sodium" may indicate an increase in their resistance to the drug, and this determines the expediency of periodic repeated acute experiments in order to verify the relevance of previously established DL50 of sodium warfarin. According to DL50 upon intragastric administration to female rats, which are the most sensitive species of animals to it, warfarin sodium belongs to highly hazardous substances.